The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3748/wjg.v23.i19.3546
|View full text |Cite
|
Sign up to set email alerts
|

Nissen fundoplicationvsproton pump inhibitors for laryngopharyngeal reflux based on pH-monitoring and symptom-scale

Abstract: AIMTo compare the outcomes between laparoscopic Nissen fundoplication (LNF) and proton pump inhibitors (PPIs) therapy in patients with laryngopharyngeal reflux (LPR) and type I hiatal hernia diagnosed by oropharyngeal pH-monitoring and symptom-scale assessment.METHODSFrom February 2014 to January 2015, 70 patients who were diagnosed with LPR and type I hiatal hernia and referred for symptomatic assessment, oropharyngeal pH-monitoring, manometry, and gastrointestinal endoscopy were enrolled in this study. All o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
0
24
1
4
Order By: Relevance
“…Comparing the 25 patients in the anti-reflux surgery group and 28 patients in the PPI group with extraesophageal manifestations, improvements in RSI score (P<0.005) and symptom scores of cough (P=0.032), mucus (P=0.011), and throat clearing (P=0.022) were significantly superior in the surgery group to those in the PPI group [9]. A systemic review and meta-analysis pooled data from 21 reports and reported GERD-related chronic laryngitis patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the 25 patients in the anti-reflux surgery group and 28 patients in the PPI group with extraesophageal manifestations, improvements in RSI score (P<0.005) and symptom scores of cough (P=0.032), mucus (P=0.011), and throat clearing (P=0.022) were significantly superior in the surgery group to those in the PPI group [9]. A systemic review and meta-analysis pooled data from 21 reports and reported GERD-related chronic laryngitis patients.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of GERD reached 7.3% in 2008, with a mean annual increase of 15.3% in Korea [4]. In Western countries, GERD is typically treated with a proton pump inhibitor (PPI) and fundoplication [567891011]. Despite numerous studies reporting the effectiveness of surgical treatment, medication-oriented treatment remains the mainstay because of a lack of awareness of surgical treatment in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric fundoplication is effective in significantly reducing acid reflux in an obese cohort [ 23 ]. It provides improved resolution of reflux compared to PPI therapy for GERD with or without an associated hiatus hernia [ 24 , 25 ]. Gastric bypass operations for morbid obesity have also been shown to reduce acid reflux, in addition to reducing BMI and metabolic conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…94 More recent studies confirm those findings. [95][96][97] A review of the surgical treatment for patients with chronic cough, LPR, and asthma found a surgical FP success rate between 48% and 94%. 98 The same group published a more recent review; according to a weighted mean per study per patient then compiled, 83.0% of patients (95% CI: 79.7-86.3%) experienced improvement, and 67.0% of patients (95% CI: 64.1-69.9%) experienced a resolution of symptoms.…”
Section: Surgical Management In Lprmentioning
confidence: 99%